Does Regional Lung Strain Correlate With Regional Inflammation in Acute Respiratory Distress Syndrome During Nonprotective Ventilation? An Experimental Porcine Study*. Issue 6 (June 2018) - Retamal, Jaime; Hurtado, Daniel; Villarroel, Nicolás; Bruhn, Alejandro; Bugedo, Guillermo; Amato, Marcelo Britto Passos; Costa, Eduardo Leite Vieira; Hedenstierna, Göran; Larsson, Anders; Borges, João Batista
Abstract : Objective: It is known that ventilator-induced lung injury causes increased pulmonary inflammation. It has been suggested that one of the underlying mechanisms may be strain. The aim of this study was to investigate whether lung regional strain correlates with regional inflammation in a porcine model of acute respiratory distress syndrome. Design: Retrospective analysis of CT images and positron emission tomography images using [ 18 F]fluoro-2-deoxy-D-glucose. Setting: University animal research laboratory. Subjects: Seven piglets subjected to experimental acute respiratory distress syndrome and five ventilated controls. Interventions: Acute respiratory distress syndrome was induced by repeated lung lavages, followed by 210 minutes of injurious mechanical ventilation using low positive end-expiratory pressures (mean, 4 cm H2 O) and high inspiratory pressures (mean plateau pressure, 45 cm H2 O). All animals were subsequently studied with CT scans acquired at end-expiration and end-inspiration, to obtain maps of volumetric strain (inspiratory volume – expiratory volume)/expiratory volume, and dynamic positron emission tomography imaging. Strain maps and positron emission tomography images were divided into 10 isogravitational horizontal regions-of-interest, from which spatial correlation was calculated for each animal. Measurements and Main Results: The acute respiratory distress syndrome model resulted in a decrease in respiratory system compliance (20.3 ± 3.4 to 14.0 ± 4.9 mL/cm H2 O; p < 0.05) and oxygenation (PaO2 /FIO2, 489 ± 80 to 92 ± 59; p < 0.05), whereas the control animals did not exhibit changes. In the acute respiratory distress syndrome group, strain maps showed a heterogeneous distribution with a greater concentration in the intermediate gravitational regions, which was similar to the distribution of [ 18 F]fluoro-2-deoxy-D-glucose uptake observed in the positron emission tomography images, resulting in a positive spatial correlation between both variables (median R 2 = 0.71 [0.02–0.84]; p < 0.05 in five of seven animals), which was not observed in the control animals. Conclusion: In this porcine acute respiratory distress syndrome model, regional lung strain was spatially correlated with regional inflammation, supporting that strain is a relevant and prominent determinant of ventilator-induced lung injury. Abstract : Supplemental Digital Content is available in the text.